Frequency response of interface states on ZnO-Au varactors. Part 1 - (:unkn) unknown (Publ by Marcel Dekker Inc, New York, NY, United States, 1994)
It was determined that the frequency responses of copper and lithium doped ZnO-Au varactors were different since the C-V characteristics of Li-doped samples were bias independent at frequencies higher than 100KHz., while the Cu doped were displaying the most variation at about the same region. Moreover, investigations on the higher frequency response of the Li-doped samples revealed that the devices were displaying a new property, originating from some impedance variations by exhibiting 'loops' on the Network analyzer at 1-110 MHz frequency region. Furthermore, it has been proved by repeated experiments that 'looping' procedure was only one of the properties of Li-doped ZnO single crystal and gold interface. Although, Cu-doped ZnO-Au devices didn't exhibit any 'loop' they did display fairly good varactor characteristics at the same frequency range. It was also shown that the doping profiles of Cu and Li-doped Schottky contacts were not the same, at which ZnO:Cu-Au and ZnO:Li-Au samples coincided to inhomogeneous and homogeneous doping profiles respectively.